Kebijakan Hukum Pemerintah Provinsi Jambi dalam Penyelenggaraan Kesejahteraan Sosial bagi Suku Anak Dalam - Putra, Anas Agusmi; Amir, Latifah (Mendapo: Journal of Administrative Law, 2022)
The Implementation of Social welfare is a part of regional government authority based on desentralitation principle. The social walfare Act number 11 on 2009 has various aim to reach peoples well beeing for all the people including Komunitas Adat Terpencil with Suku Anak dalam is a part of it. As far as we know there is no legal policy from Jambi Province government yet, revers to social welfare implementation for Suku Anak Dalam. A courding to article 18 verse 6 of 1945 indonesian constitution and based on local authonomy sistem, jambi province government must determine a policy that will give the benefit of SAD cummunity as legal protection for there social problem. The aims of this legal research is to analyze the authority and function of jambi province government relate to social welfare implementation for SAD society. As legal research use the primair, secondair and tertier legal materials that would be analyzed by interpretation and evaluation those legal materials based on relevan legal theoris to made conclutian as the answer of the problem.